2011
DOI: 10.1002/mawe.201100733
|View full text |Cite
|
Sign up to set email alerts
|

Controlled reduction of palladium nanoparticles on surface of chemically modified silicas

Abstract: The reduction of palladium ions by silicon hydride groups grafted to the surface of silica matrices was applied for the synthesis of palladium-containing nanocomposites. Ordered mesoporous silicas, such as MCM-41 and SBA-15, along with silochrom type silica were used as supports for palladium nanoparticles in order to obtain encapsulated in pores metal particles. The synthesized nanocomposites have been studied by IR-spectroscopy, X-ray diffraction analysis, low-temperature nitrogen adsorption and transmission… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 21 publications
2
2
0
Order By: Relevance
“…It has been reported that the Si-H groups enable reduction of Pd 2þ , Cu þ , Cu 2þ to the metallic states in organic or aqueous conditions. [31][32][33] On the other hand, the unreacted Si-H bonds were hydrolyzed to form Si-OH bonds, and subsequently condensed to constitute Si-O-Si bonds in aqueous condition, which is consistent with the newly appeared Si-O-Si peak (1100 cm À1 ). 32 In addition, it should be cited from the previous report 22 that the nucleophilic attack on Si atoms by -OH ions under NaOH deactivation condition hydrolyzes the silazane Si-N framework in the PVSZ to the siloxane Si-O-Si skeletal structure via condensation reaction of intermediately formed silanol, eventually leading to the phase conversion from PVSZ surface to silicate glass surface.…”
Section: A Reductive Synthesis Of Au Nps On the Pvsz Surfacesupporting
confidence: 69%
See 1 more Smart Citation
“…It has been reported that the Si-H groups enable reduction of Pd 2þ , Cu þ , Cu 2þ to the metallic states in organic or aqueous conditions. [31][32][33] On the other hand, the unreacted Si-H bonds were hydrolyzed to form Si-OH bonds, and subsequently condensed to constitute Si-O-Si bonds in aqueous condition, which is consistent with the newly appeared Si-O-Si peak (1100 cm À1 ). 32 In addition, it should be cited from the previous report 22 that the nucleophilic attack on Si atoms by -OH ions under NaOH deactivation condition hydrolyzes the silazane Si-N framework in the PVSZ to the siloxane Si-O-Si skeletal structure via condensation reaction of intermediately formed silanol, eventually leading to the phase conversion from PVSZ surface to silicate glass surface.…”
Section: A Reductive Synthesis Of Au Nps On the Pvsz Surfacesupporting
confidence: 69%
“…[31][32][33] On the other hand, the unreacted Si-H bonds were hydrolyzed to form Si-OH bonds, and subsequently condensed to constitute Si-O-Si bonds in aqueous condition, which is consistent with the newly appeared Si-O-Si peak (1100 cm À1 ). 32 In addition, it should be cited from the previous report 22 that the nucleophilic attack on Si atoms by -OH ions under NaOH deactivation condition hydrolyzes the silazane Si-N framework in the PVSZ to the siloxane Si-O-Si skeletal structure via condensation reaction of intermediately formed silanol, eventually leading to the phase conversion from PVSZ surface to silicate glass surface. At here, it is important to point out that the reductive Si-H functional groups on the surface of cured PVSZ acted as surface bound reducing agents to form directly Au NPs in the presence of Au precursor (HAuCl 4 ) solution, leading to formation of Au NPs adhered to silicate (Au NPs-silicate) glass surface by subsequent hydrolysis.…”
Section: A Reductive Synthesis Of Au Nps On the Pvsz Surfacesupporting
confidence: 69%
“…The effect of modifying functional groups on the adsorption properties of silicas and the catalytic activity of deposited metal phases on such supports is of particular interest [14][15][16][17][18][19][20][21][22][23][24][25]. Various combinations in the modification of supports open up wide possibilities for the obtainment of new and more efficient catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…The catalyst showed high activity in three different processes: carbonylation of iodarenes, and Heck and Suzuki combination reactions. Silica modified with silicon hydride groups can be used for the synthesis of palladium nanoparticles on the surface and in the pores of the silica matrix [21]. Palladium catalysts on a silica matrix functionalized with mercapto or diphenylphosphine can be successfully used for the synthesis of biaryls in the Suzuki-Miyaura reaction [22].…”
Section: Introductionmentioning
confidence: 99%